'Scripted fantasies': writing the twenty-first century. Issue 3 (4th March 2022) - Childs, Peter
ABSTRACT: If fiction is seldom perceived to be a contemporary form oriented towards global, ecological, or nonhuman concerns, it documents and dramatises crises, particularly of identity, that demonstrate these contexts. The twenty-first century novel both reflects and seeks to influence ethical, philosophical and critical discussion while negotiating its status as a medium that gained a strong cultural foothold because it addressed the establishment and imposition of civilizational norms in human societies from the Enlightenment through to the twentieth century. This essay considers how novels have approached challenges to human and humanist centrality from a range of forces in the last twenty years as multiple debates have taken a nonhuman turn.